Exploration of cerebral vasospasm from the perspective of microparticles - Gao, Yalong; Li, Kai; Li, Xiaotian; Li, Qifeng; Wang, Jiwei; Zhang, Shu; Zhang, Jianning (Frontiers in Neuroscience, 2022)
Cerebral vasospasm is a frequently encountered clinical problem, especially in patients with traumatic brain injury and subarachnoid hemorrhage. Continued cerebral vasospasm can cause cerebral ischemia, even infarction and delayed ischemic neurologic deficits. It significantly affects the course of the disease and the outcome of the patient. However, the underlying mechanism of cerebral vasospasm is still unclear. Recently, increasing studies focus on the pathogenic mechanism of microparticles. It has been found that microparticles have a non-negligible role in promoting vasospasm. This research aims to summarize the dynamics of microparticles in vivo and identify a causal role of microparticles in the occurrence and development of cerebral vasospasm. We found that these various microparticles showed dynamic characteristics in body fluids and directly or indirectly affect the cerebral vasospasm or prompt it. Due to the different materials carried by microparticles from different cells, there are also differences in the mechanisms that lead to abnormal vasomotor. We suggest that microparticle scavengers might be a promising therapeutic target against microparticles associated complications.